Building a pedagogical practice: learning to learn with science teaching in the Semear Hospital Class - Marinho Pedrosa, Emerson; Adriano Schwingel, Paulo (Seven Editora, 2023)
With the implementation of its first Hospital Class in 2015, the state of Pernambuco took the first step towards the inclusion of children and adolescents towards ensuring schooling for students in a state of illness and hospitalized for health treatment. The thesis brought a qualitative research, of the case study type, associated with a theoretical-scientific survey in the hospital context, having carried out an analysis with the objectives of seeking to understand Hospital Pedagogy as a distinguished proposal in the construction of knowledge, through contexts of learning for teacher training, the inclusion and schooling of the student/patient inserted in the special education section of the Municipal Teaching Network of Recife. With the purpose of accessing this environment through science teaching, we learned to learn with Semear by examining the collected material, using discursive textual analysis as an aid to understand the phenomena investigated in the Class. Backed by theoretical references, the work clarifies the development of this teaching modality in the Pernambuco State, the legal bases that guides it in Brazil, its discussion on special and inclusive education, and the character of specialized teacher training that should comprise this space of health and schooling as a space for interdisciplinary humanized care, bringing results where the role of science education is promising for the understanding of the world of students and their daily relationships, woven by behavioral attitudes towards the facts of life, made possible by the humanization characteristic of the Class, which enables the generation of meaningful learning for students/patients. In conclusion, the relevance of educational inclusion for children who need care should permeate education and health, a binomial of inclusion in the Hospital Class throughout the State of Pernambuco. DOI: 10.56238/pacfdnsv1-005